The Trade Reducing Effects of Restrictions on Liner Shipping - Bertho, Fabien; Borchert, Ingo; Mattoo, Aaditya (Elsevier, 2016)
The costs of shipping containerized cargo on liner vessels play a pivotal role in determining a country's integration into international trade. We examine how policy governing the liner shipping sector affects maritime transport costs and seaborne trade flows. Using a novel data set of services trade policy information, we find that restrictions, particularly on foreign investment, significantly increase maritime transport costs. The cost-inflating effect ranges from 26% to 68%, and the resultant reduction in trade flows from 48% to 77%, depending on the level of restrictiveness. We estimate the elasticity of seaborne trade flows with respect to distance to be nearly unity, and are able to disentangle the direct effect of distance from the one that is operating indirectly through higher maritime transport costs. Since the bulk of global merchandise goods trade is seaborne, the magnitude of frictions identified in this paper and their spatial distribution have ramifications for connectivity and growth.